IGF-1 Response to Arm Exercise with Eccentric and Concentric Muscle Contractions in Resistance-Trained Athletes with Left Ventricular Hypertrophy - Żebrowska, A.; Waśkiewicz, Z.; Zając, A.; Gąsior, Z.; Galbo, H.; Langfort, J. (International Journal of Sports Medicine, 2013)
The study aimed at evaluating changes in plasma levels of insulin-like growth factor 1 (IGF-1), insulin-like growth factor binding protein-3 (IGFBP-3), testosterone, growth hormone (GH), cortisol, and insulin in resistance-trained male athletes with (n=9) and without (n=9) left ventricular hypertrophy (LVH) in response to eccentric (ECC) and concentric (CON) arm exercise. 10 age-matched healthy non-trained subjects served as controls. M-mode and 2D Doppler echocardiography were used to estimate LV mass.Resting IGF-1 concentration was higher in LVH athletes compared to controls (52±5 nM vs. 46±7 nM, p<0.05). ECC exercise resulted in higher (p<0.05) serum IGF-1 concentrations in athletes with LVH (70±11 nM, n=9) compared to those without LVH (62±10 nM, n=9), and to untrained controls (54±6 nM). Both CON and ECC exercise resulted in higher serum IGFBP-3 levels in LVH athletes compared to controls (242±57 and 274±58, athletes, vs. 215±63 and 244±67, controls, nM, p<0.05). In ECC exercise, GH concentrations were lower in LVH than in non-LVH athletes (4.7±2.1 vs. 6.1±1.8 ng · mL − 1, p<0.05). No differences in other hormones were found between groups. In conclusion, LVH is accompanied by elevated resting serum IGF-1 and enhanced response to eccentric arm exercise. These findings suggest a role of IGF-1, possibly released from contracting muscle, in stimulating LV hypertrophy in resistance training.
Keywords: echocardiography; heart; insulin-like growth factor 1; resistance training; eccentric exercise